(untitled) (Journal of the College of Languages (JCL), 2010)
Emily Bronte is born in Yorkshire on 30 July 1818. Her father, Rev. Patrick Bronte, is a man of intelligence and determination which enables him to gain an admission as a sizar to 81. John’s Cambridge in 1802. He has six children where Emily is the fifth. The mother is a young beautiful girl who belong to an important family. Both Emily’s parents try to teach Their children well, support them all the time and elevate them to "-.../ high levels. This causes an eagerness towards reading and writing, but the happiness of the children is affected by the sickness and later on by the death of their mother in 1821. After that things would never be the same as the father keeps himself away with his studies and Parish’s work. The only compensation for children becomes the love they have for each other (Herbert Read, Charlotte and Emily Bronte, PP.145-8).